Reliability assessment of shear-deficient reinforced concrete beams externally bonded by FRP sheets having different configurations. (June 2020) - Shahriari, S.; Naderpour, H.
Abstract: In this paper, a reliability and sensitivity analysis has been carried out based on a large experimental database having different samples. The samples used for the study include a control beam, and three main shear strengthened beams having full wrap of the cross-section (W), U jacketing along three sides (U), and side bonding (S). The effect of shear steel, concrete strength, and applied load is investigated on the reliability index. Then, a sensitivity analysis has been done for constant and random variables. Reliability analysis has been performed with two methods (FORM and Monte Carlo sampling). The results indicate that the full wrap configuration is the least reliable parameter compared to the other configurations. Furthermore, the FRP modulus of elasticity (Ef ) is the most effective variable in the variation of probability of failure.